Clinical applications of custom-made vaginal cylinders constructed using three-dimensional printing technology - Sethi, Rajni; Cunha, Adam; Mellis, Katherine; Siauw, Timmy; Diederich, Chris; Pouliot, Jean; Hsu, I-Chow (Journal of Contemporary Brachytherapy, 2016)
Purpose : Three-dimensional (3D) printing technology allows physicians to rapidly create customized devices for patients. We report our initial clinical experience using this technology to create custom applicators for vaginal brachytherapy. Material and methods : Three brachytherapy patients with unique clinical needs were identified as likely to benefit from a customized vaginal applicator. Patient 1 underwent intracavitary vaginal cuff brachytherapy after hysterectomy and chemotherapy for stage IA papillary serous endometrial cancer using a custom printed 2.75 cm diameter segmented vaginal cylinder with a central channel. Patient 2 underwent interstitial brachytherapy for a vaginal cuff recurrence of endometrial cancer after prior hysterectomy, whole pelvis radiotherapy, and brachytherapy boost. We printed a 2 cm diameter vaginal cylinder with one central and six peripheral catheter channels to fit a narrow vaginal canal. Patient 3 underwent interstitial brachytherapy boost for stage IIIA vulvar cancer with vaginal extension. For more secure applicator fit within a wide vaginal canal, we printed a 3.5 cm diameter solid cylinder with one central tandem channel and ten peripheral catheter channels. The applicators were printed in a biocompatible, sterilizable thermoplastic. Results : Patient 1 received 31.5 Gy to the surface in three fractions over two weeks. Patient 2 received 36 Gy to the CTV in six fractions over two implants one week apart, with interstitial hyperthermia once per implant. Patient 3 received 18 Gy in three fractions over one implant after 45 Gy external beam radiotherapy. Brachytherapy was tolerated well with no grade 3 or higher toxicity and no local recurrences. Conclusions : We established a workflow to rapidly manufacture and implement customized vaginal applicators that can be sterilized and are made of biocompatible material, resulting in high-quality brachytherapy for patients whose anatomy is not ideally suited for standard, commercially available applicators.